Validación de un método ágil para el análisis de riesgos de la información digital (2011)
The lack of a culture of risk analysis for digital assets can be frequently observed in small technology businesses. In large part, this is due to the high cost of implementation using known methods that require sacrifices in time and effort and that, in many cases, are greater than a business’s capacities. This is why a method was designed and validated that allows small businesses to include risk analysis of digital information in their processes. The method avoids excessive consumption of resources, a characteristic of traditional methods and methodologies. The implementation and validation of the method and its information technology tools were applied in five businesses with different characteristics. The satisfactory results were reflected in the indicators for productivity, efficiency and effectiveness that were designed in the context of applied experimental design.